Light scattering effect of submicro-textured Ag/Al composite films prepared at lower substrate temperatures - 唐平林 吴永刚 童广德 夏子奂 刘仁臣 梁钊铭 周建 (Chinese physics B, 2013)
We present a new and practical approach for preparing submicro-textured silver and aluminum （Ag/Al） double-structured layers at low substrate temperatures. The surface texturing of silver and aluminum double-structured layers was performed by increasing the deposition temperature of the Al layers to 270℃. The highly submicro-textured silver and aluminum double-structured layers were prepared by thermal evaporation on quartz glasses and their surface microstructure, light scattering properties, and thermal stability were investigated. Results showed that the highly submicro-textured Ag/Al composite films prepared at low substrate temperatures used as back reflectors not only can enhance the light scattering and have good thermal stability, but also have good adhesion properties. In addition, their fabrication is low cost and readily carried out.